PRODUKTIVITAS DAN BIAYA PENGANGKUTAN TIGA JENIS TRUK ANGKUTAN KAYU DI TIGA HAK PENGUSAHAAN HUTAN DI KALIMANTAN BARAT - Sukanda Sukanda; Dulsalam Dulsalam; Ishak Sumantri (Jurnal Penelitian Hasil Hutan, 1989)
An investigation on hauling productivities and hauling costs of three types of log hauling trucks was carried out at three logging companies in West Kalimantan in 1988. Three types of logging trucks, i.e. Nissan with semi trailer, Berliet with semi trailer and Nissan truck, were observed. The productivities of trucks were gathered through time study while the hauling costs were calculated based on secondary data. The purpose of the investigation is to find hauling productivities, operating costs of trucks and hauling costs.The results of the investigation are as follows :The average hauling productivities of Nissan with semi trailer, Berliet with semi trailer and Nissan trucks are 484,99m3 km/hour, 492,02 m3 km/hour and 292,07 m3 km/hour, respectively .The average hauling costs of Nissan with semi trailer, Berliet with semi trailer and Nissan Trucks are Rp. 63,08/m3 km, Rp. 64,66/m3 km and Rp. 84,39/m3 km, respectively.The differences in both the hauling productivities and hauling costs either between Nissan logging truck with semi trailer and Nissan loging truck or between Berliet logging truck with semi-trailer and Nissan logging truck were highlysignificant because of the differences in logging truck capacities, transport distances and driver skills. But the hauling productivities and hauling costs between Berliet logging truck with semi-trailer and Nissan logging truck with semi trailer did not differ significantly because the logging truck capacities, transport distance and driver skill in PT. Kawedar are comparatiuely simmilar to those in PT. Erna Juliawati.Hauling costs by using smallar trucks are more expensive than those by using larger trucks